RADICAL APPRAISAL TYPOLOGY: MAPPING ONLINE OFFENSIVE LANGUAGE ON RELIGIOUS MODERATION VIOLATIONS - Arkin Haris; Shabrina An Adzhani (Leksema: Jurnal Bahasa dan Sastra, 2025)
This study investigates how the evaluative system of Appraisal Theory is applied to analyse offensive language within the digital discourse of religious moderation. It addresses the research gap in previous studies that have not systematically linked linguistic evaluation with religion based hate speech. The data consist of social media comments containing violations of religious moderation principles and were analysed qualitatively using the frameworks of offensive language (Zhao and Hovy 2020), Appraisal Theory (Martin and White 2005), and the moderation framework of the Indonesian Ministry of Religious Affairs (Kemenag 2019). The findings identify four key types of offensive expression that constitute the Radical Appraisal Typology namely Direct Emotional Offense, Implicit Moral Offense, Cultural Appreciation Offense, and Closed Engagement Offense. These categories represent an evaluative spectrum ranging from overt emotional aggression to implicit moral and ideological exclusion. Theoretically, the study extends the application of Appraisal Theory to the domain of religion based hate speech by revealing how intensification and mitigation mechanisms shape the evaluative force of language. Practically, it underscores the importance of linguistic awareness as a foundation for promoting religious moderation, tolerance, and national cohesion in digital public discourse.